Ocean Basket:Exploration Of The Impact Sustainable Fishing Practices Have On Brand Loyalty - Steenkamp, Sherilee (The IIE, 2019)
The purpose of this study is to explore the impact sustainable fishing practices have on the brand loyalty of Ocean Basket’s consumers. Now that brands are being held accountable for their environmental impact and forced to address social issues,that the public sector fails to address; it is not clear whether brands benefit when making these strategic changes to be in harmony with the natural environment.To address the research problem and determine whether consumers purposefully choose Ocean Basket for addressing overfishing, quantitative research will be used with a positivist paradigm and survey research design. The Theory of Reasoned Action will be tested to determine whether consumers’ attitudes and behaviour change when learning about Ocean Baskets’ commitment to sustainable fishing. Questionnaires will be used to collect data and capture the data in a cost-and time-effective way and will be analysed using a grid and coding system with cross-tabulation, to establish the association between the variables:sustainable fishing practices and brand loyalty.It was found that sustainable fishing practices have a favourable impact on the brand loyalty of Ocean Basket. This study contributes to how consumers resonate with environmentally sustainable brands and inspire further research on how brands can resonate with consumers by being in harmony with the natural environment.
Keywords: Brand; Brand loyalty; Sustainable fishing; Sustainability